1997
DOI: 10.1017/s0954394500001794
|View full text |Cite
|
Sign up to set email alerts
|

Defining the envelope of linguistic variation: The case of “don't count” forms in the copula analysis of African American Vernacular English

Abstract: Ever since Labov, Cohen, Robbins, and Lewis's (1968) pioneering study, it has been commonplace to set aside certain tokens in analyzing variability in the English copula as “don't count” (DC) forms. These cases are most often occurrences of the copula that exhibit categorical behavior (as with the full copula in clause-final position), as well as those that are ambiguous or indeterminate. In this article, I propose a set of copula forms that should be set aside from variable analysis as instances of DC forms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 13 publications
1
54
0
Order By: Relevance
“…However, researchers examining varieties such as Samaná English (see Poplack & Sankoff, 1987) and Trinidadian Creole (see Winford, 1992a) have observed variable copula absence in these environments and have included them in their analyses. 23 Blake (1997) argued that wit constructions should be considered "don't count" cases in studies of aave copula variability, not only because of their near-categorical behavior, but also because of their tendency to occur with extremely high frequencies in the data. "Adding these cases to the count tokens would account for 51% (n ϭ 1703) of the data.…”
Section: Rd Person Singular Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, researchers examining varieties such as Samaná English (see Poplack & Sankoff, 1987) and Trinidadian Creole (see Winford, 1992a) have observed variable copula absence in these environments and have included them in their analyses. 23 Blake (1997) argued that wit constructions should be considered "don't count" cases in studies of aave copula variability, not only because of their near-categorical behavior, but also because of their tendency to occur with extremely high frequencies in the data. "Adding these cases to the count tokens would account for 51% (n ϭ 1703) of the data.…”
Section: Rd Person Singular Variationmentioning
confidence: 99%
“…It has also been argued that this environment is likely to create difficulties in distinguishing contraction from absence while coding (see, e.g., Wolfram, 1969). By contrast, Blake (1997) argued in favor of their inclusion, noting that they caused only minimal coding difficulties in the aave data that she con- …”
Section: Rd Person Singular Variationmentioning
confidence: 99%
“…Later cross-variety comparisons of hierarchies of past inflection according to morphological category include Blake (1997a:158), Patrick (1999:246), Poplack and Tagliamonte (2001:121), and Hackert (2004:159). Whereas Blake (1997a) and Hackert (2004) have followed (and modified) Winford's categorization of verbs (1992), which, in turn, is based on Fasold (1972), Patrick (1999) is based on Patrick (1992). As Table 5 shows, however, there are other models as well.…”
Section: Morphological Verb Categoriesmentioning
confidence: 99%
“…in copula analyses is presented in Blake (1997b). My article aims to contribute to variation analysis in the spirit of these studies.…”
mentioning
confidence: 99%
“…A second consideration is the method of calculation for ain't. To my knowledge, this issue has largely been neglected, in sharp contrast with studies of the copula, in which the method of calculation remains controversial (Blake, 1997;Rickford, Ball, Blake, Jackson, & Martin, 1991;Walker, 2000aWalker, , 2000b. For example, Rickford et al (1991) showed that the choice of method can drastically affect the results obtained.…”
Section: T H E a I N ' T C O N S T R A I N Tmentioning
confidence: 99%